3(x+2)=5(x+1)-(2x-1)

Simple and best practice solution for 3(x+2)=5(x+1)-(2x-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x+2)=5(x+1)-(2x-1) equation:


Simplifying
3(x + 2) = 5(x + 1) + -1(2x + -1)

Reorder the terms:
3(2 + x) = 5(x + 1) + -1(2x + -1)
(2 * 3 + x * 3) = 5(x + 1) + -1(2x + -1)
(6 + 3x) = 5(x + 1) + -1(2x + -1)

Reorder the terms:
6 + 3x = 5(1 + x) + -1(2x + -1)
6 + 3x = (1 * 5 + x * 5) + -1(2x + -1)
6 + 3x = (5 + 5x) + -1(2x + -1)

Reorder the terms:
6 + 3x = 5 + 5x + -1(-1 + 2x)
6 + 3x = 5 + 5x + (-1 * -1 + 2x * -1)
6 + 3x = 5 + 5x + (1 + -2x)

Reorder the terms:
6 + 3x = 5 + 1 + 5x + -2x

Combine like terms: 5 + 1 = 6
6 + 3x = 6 + 5x + -2x

Combine like terms: 5x + -2x = 3x
6 + 3x = 6 + 3x

Add '-6' to each side of the equation.
6 + -6 + 3x = 6 + -6 + 3x

Combine like terms: 6 + -6 = 0
0 + 3x = 6 + -6 + 3x
3x = 6 + -6 + 3x

Combine like terms: 6 + -6 = 0
3x = 0 + 3x
3x = 3x

Add '-3x' to each side of the equation.
3x + -3x = 3x + -3x

Combine like terms: 3x + -3x = 0
0 = 3x + -3x

Combine like terms: 3x + -3x = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 1/3r-20=-5 | | 3x^5-7x^4+6x^2-14x=0 | | 3(x+2)=5(x+1)-2(x-1) | | 4x-4=-5x-20 | | 40-21(3x+5)-12(3-5x)+8=0 | | 13+4(6x-5)=5(5x+2) | | 4-7=18-x | | x+40=-9 | | 4-7I=18/x | | 25x-16-9x=20+24x-10-10x | | 2t+11-4t=13 | | 12x+15=9x+15 | | 7x-(-8x+12-(24x+12)-2)=9x+62 | | 2(x+4)-12=20 | | 45.99(207.96/100)=4 | | 7x+8x+12-24x-12-2=9x+62 | | 3x-6=4x+4-13 | | 8-3h=2 | | 9x-15y=75 | | =12a(2/3+102/5) | | 39x+12=9x+62 | | 45x-20x= | | 3x-15=-3x-3 | | 2log*9(x)=log*9(8)+log*9(x-2) | | 7x-6+3x-5=8x+5-10x-4 | | 148.75=9.25(-6+t) | | 2log^9(x)=log^98+log^9(x-2) | | 27r^2+17n+72=0 | | x+(x+2)=-67 | | log^4[log^4(2x)]=1 | | 0=x^2+26+48 | | log(x)+log(x+5)=log(6x+12) |

Equations solver categories